FROM THE PEASENT TO THE FAMILY FARMER: THE ACESS TO INSTITUTIONAL MARKETS FROM PNAE (Social and Environmental Law Journal, 2023)
This article discusses the role of a public policy in the Programa Nacional de Alimentação Escolar as a way to integrate the peasant into the market in the current capitalist and excluding scenario. For that, the deductive method and the bibliographic technique were used. The study goes thought the question of the peasantry, the differentiation and transformation of the peasent into a family farmer, starting from his insertion in the capitalist system. It is considered that such inclusion was possible, above all, from programs such as the PNAE, though wich it is prescribed that, at least, 30% of federal resources destined for the acquisition of school meals must be acquired from family farming. From that, the notion of development is questioned. Thus, it is evidente that the promotion and creation of public policies such as the one studied are positive for local and sustainable rural development.